Trade openness and unemployment in selected Southern African Development Community (SADC) countries - Dorcas Gonese; Kin Sibanda; Phillip Ngonisa (Economies, 2023)
The relationship between trade openness and unemployment in Southern African Development Community (SADC) countries remains an area of significant interest and concern. While trade openness is often advocated for fostering economic growth and development, its potential effects on employment outcomes are complex and multifaceted. Understanding the nature and nuances of this relationship within the SADC region is crucial for policymakers and stakeholders seeking to design effective strategies that balance the benefits of trade openness with the goals of reducing unemployment and promoting inclusive growth. This study evaluates the effect of trade openness on unemployment in SADC from 1980 to 2019 using panel ARDL (pooled mean group-PMG) estimation techniques. The findings of the study show that trade openness and exports negatively impact unemployment, whereas imports positively affect unemployment in the long run. This suggests that while boosting exports and real trade, openness decreases unemployment, and imports increase job losses in the long run in the SADC region. This calls for more caution on trade openness regarding what to export and import when addressing regional unemployment reduction policies.
Keywords: 330; unemployment; trade openness; panel data; pooled mean group; SADC